(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
As in any process, the formation of humane qualities in younger students goes through certain stages. Subtasks are solved at each stage based on an organic unit. The solution of partial tasks is aimed at achieving a single goal. The process of formation of humane qualities in junior schoolchildren is essentially carried out in four stages. The article talks about the stages of the formation of humane qualities in elementary school students.